Employment and return to work following chemoradiation in patient with HPV-related oropharyngeal cancer. Issue 1 (December 2016) - Baxi, Shrujal; Salz, Talya; Xiao, Han; Atoria, Coral; Ho, Alan; Smith-Marrone, Stephanie; Sherman, Eric; Lee, Nancy; Elkin, Elena; Pfister, David
Abstract Background Human papillomavirus (HPV)-positive oropharyngeal cancer primarily affects working-age adults. Chemotherapy and radiation (CTRT) used to treat this disease may adversely impact a survivors' ability to work after treatment. Methods We surveyed participants with HPV-positive oropharyngeal cancer who completed CTRT regarding employment. We examined the associations between 1) sociodemographic and clinical factors and employment outcomes, and 2) health-related quality of life and satisfaction with ability to work. Results 102 participants were employed full-time at diagnosis for pay and surveyed at a median of 23 months post-CTRT (range 12–57 months). The median age at diagnosis was 57 years (range 25–76 years). During CTRT, 8 % stopped working permanently, 89 % took time off or reduced responsibility but later returned, and 3 % reported no change. For those who took time off but returned, median time to return to work was 14.5 weeks. In multivariable analysis, younger age predicted for needing more than the median time off. At time of survey, 85 % participants were working, 7 % had retired, and 8 % were not working for other reasons. Seventeen percent of participants were not satisfied with their current ability to work, which was associated with poorer health-related quality of life and persistent treatment toxicities (p < 0.001). Conclusions CTRT interrupts employment in the majority of working patients with HPV-positive oropharyngeal cancer but most return. However, treatment-related toxicities might lead to dissatisfaction with ability to work.